Forecasting of the Malaysian Betas - Ho, Catherine, Soke Fun; Chen, Yin Foo (INTI International University, 2009)
Estimating beta is a straightforward application of the market model. However, investors are interested in the historical value of betas only in the hope of better able to forecast the probable future value. The issue of beta forecasting is explored using segmented Malaysian industries data. Four forecasting techniques are used to evaluate the forecasting ability of historical betas. The techniques included the commonly accepted Blume and Vasicek methods, a naive constant model and a technique widely used by commercial providers. These accuracy and suitability of these predicted betas will be examined with the MSE criteria. It is observed that the commercial model adjustments greatly improve the MSE performance in both periods. Specifically it reduces the inefficiency element of the MSE components.